2019
DOI: 10.12795/pixelbit.2019.i55.09
|View full text |Cite
|
Sign up to set email alerts
|

La eficacia de la Realidad Aumentada en las aulas de Infantil: un estudio del aprendizaje de SVB y RCP en discentes de 5 años

Abstract: índice 1.-Learning of audacity for the edition and production of digital didactic contents // El aprendizaje de Audacity para la edición y producción de contenidos didácticos digitales J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…Although educational experiences have been developed with AR to a greater extent than VR, amongst other reasons because the former does not require special devices to interact with objects, a diversity of experiences are actually beginning to appear, which combine them both so that they can be applied to different scientific fields: engineering and architecture [5]; language learning [6]; education sciences [7]; chemistry [8]; natural sciences [9]; biology [10]; geography [11]; medicine [12][13][14]; emergency protocol learning [15]; or physical activities [16].…”
Section: Immediate Commercial Boommentioning
confidence: 99%
“…Although educational experiences have been developed with AR to a greater extent than VR, amongst other reasons because the former does not require special devices to interact with objects, a diversity of experiences are actually beginning to appear, which combine them both so that they can be applied to different scientific fields: engineering and architecture [5]; language learning [6]; education sciences [7]; chemistry [8]; natural sciences [9]; biology [10]; geography [11]; medicine [12][13][14]; emergency protocol learning [15]; or physical activities [16].…”
Section: Immediate Commercial Boommentioning
confidence: 99%
“…De entre todas las posibilidades y ventajas que ofrece la RA, destaca el hecho de adaptarse a los ritmos individuales de aprendizaje, incluso en los casos con necesidades específicas de apoyo educativo (e.g. Merino et al, 2015;Moreno Martínez et al, 2017;López-Belmonte et al, 2019). Por lo tanto, bien utilizada, sería la herramienta ideal para trabajar a la par, tanto intervenciones con alumnos de necesidades específicas como actividades de extensión con alumnos de altas capacidades.…”
Section: Resultsunclassified
“…The present systematic review confirms that VR training improved the rate and depth of compressions in 4, [34–36,37] of the 6 articles analyzed as compared to instructor-led face-to-face BLS training. Previously-published studies in school children found that the application of virtual and augmented reality during CPR training increased CPR-skills [39,40] . In contrast to reports about a greater improvement in skills due to the use of virtual and augmented reality in CPR training in the classroom (41), Nas et al [32] described an inferior performance as compared to face-to-face training for depth of chest compressions in laypersons after VR CPR training.…”
Section: Discussionmentioning
confidence: 99%